2013
DOI: 10.1590/s1517-83822013000400002
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnology of polyketides: new breath of life for the novel antibiotic genetic pathways discovery through metagenomics

Abstract: The discovery of secondary metabolites produced by microorganisms (e.g., penicillin in 1928) and the beginning of their industrial application (1940) opened new doors to what has been the main medication source for the treatment of infectious diseases and tumors. In fact, approximately 80 years after the discovery of the first antibiotic compound, and despite all of the warnings about the failure of the “goose that laid the golden egg,” the potential of this wealth is still inexorable: simply adjust the focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 98 publications
(139 reference statements)
0
52
0
1
Order By: Relevance
“…An important tool to enhance the power of the metagenomic method is bioinformatic analysis, which supports the identification of new genes for several medical and industrial molecule pathways (Gomes et al 2013). The protein sequences exhibited identities of up to 90 % with published sequences according to BLAST analysis, and the function protein was confirmed in the Pfam database (Table 1).…”
Section: Bioinformatics Predicts Protein Functionmentioning
confidence: 99%
See 3 more Smart Citations
“…An important tool to enhance the power of the metagenomic method is bioinformatic analysis, which supports the identification of new genes for several medical and industrial molecule pathways (Gomes et al 2013). The protein sequences exhibited identities of up to 90 % with published sequences according to BLAST analysis, and the function protein was confirmed in the Pfam database (Table 1).…”
Section: Bioinformatics Predicts Protein Functionmentioning
confidence: 99%
“…Analogous approaches for screening polyketides in a soil sample from Jaboticabal, State of Sao Paulo, were carried out (Gomes et al 2013). These authors found a PKS module that exhibited homology with myxobacteria PKS type I (36 % identity and a 50 % BLASTp similarity with Chondromyces crocatus CndA protein, its closest neighbour).…”
Section: Bioinformatics Predicts Protein Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…FUNGI are prolific producers of low-molecular-weight molecules with various biological activities, such as antibiotic, immunosuppressive, cholesterol-lowering and antitumour activities [1][2][3][4][5] . In addition, fungi produce natural dyes and mycotoxins which are of importance in dye and food industry 6,7 .…”
mentioning
confidence: 99%